The outcome of Manchester operation in cervical elongation patients with pelvic organ prolapse at Dr. Soetomo Hospital, Surabaya from January 2015 to June 2017 - Mokhamad Anhar Dani; Azami Denas Azinar; Eighty Mardiyan Kurniawati; Hari Paraton; Gatut Hardianto; Tri Hastono Setyo Hadi (Universitas Airlangga, 2020)
Objectives: the aim of this study is to report the outcome of Manchester operation in cervical elongation patients with pelvic organ prolapse at Dr. Soetomo Hospital, Surabaya from January 2015 to June 2017.Case Report: During January 2015 until June 2017 there were seven patients already performed Manchester operation, however only four patients routine control. In all four cases, three cases were obtained with cervical elongation with a pelvic organ prolap (POP) and one case with cervical elongation. Perform evaluation before and after operation by using questionnaire and inspection of POP-Q system. During the evaluation there was one case with repeated lump complaints diagnosed with a uterine prolap, while one of it was with a posterior compartment prolap, but the patient did not complain during the evaluation. Both of these patients refused to reoperate after evaluation.Conclusion: After Manchester operation in cervical elongation with POP had two cases with repeated prolapse. Questionnaires and POP-Q systems were used to diagnose and evaluate preoperative and postoperative Manchester.